2013
DOI: 10.1111/lam.12092
|View full text |Cite
|
Sign up to set email alerts
|

Culture conditions and sample preparation methods affect spectrum quality and reproducibility during profiling of Staphylococcus aureus with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry

Abstract: Significance and Impact of the Study: Two culture conditions (agar or broth) and two sample preparation methods (intact cell or protein extraction) were evaluated for their effects on profiling of Staphylococcus aureus using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Results indicated that MALDI-enabled profiling of S. aureus is most effective when cultures are grown in broth and processed using a protein extraction-based approach. These findings should enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…Although the TFA sample preparation protocol has been specifically developed as a MALDI-TOF MScompatible method for microbial inactivation of HPB, it was decided not to employ this protocol. It is well-known that spectra produced by acid-based methods exhibit systematic changes compared to spectra created by the direct transfer method (41). Differences between spectra obtained by the ethanol-FA and the TFA method, however, are much smaller, since both techniques are ultimately based on acid extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Although the TFA sample preparation protocol has been specifically developed as a MALDI-TOF MScompatible method for microbial inactivation of HPB, it was decided not to employ this protocol. It is well-known that spectra produced by acid-based methods exhibit systematic changes compared to spectra created by the direct transfer method (41). Differences between spectra obtained by the ethanol-FA and the TFA method, however, are much smaller, since both techniques are ultimately based on acid extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, we extracted all of our isolates, which modestly increases the time and expense of the assay. However, extraction is known to improve spectrum reproducibility and increase the number of peaks and mass range width for S. aureus isolates (48). Finally, we did not fully evaluate whether the use of a single spectrum per isolate tested could achieve similar results.…”
Section: Figmentioning
confidence: 94%
“…J.E. Goldstein et al [4] reported that culture conditions and sample preparation prior to spectral acquisition would affect the spectrum quality of S. aureus spectra for MALDI-TOF MS identification. Therefore, in this study, the conditions including the extraction method and experimental environment were strictly controlled.…”
Section: Discussionmentioning
confidence: 99%